Atividade anti-inflamatória e antinociceptiva dos extratos brutos e frações de Eugenia uniflora e Libidibia ferrea in vivo - Falcão, Tamires Rocha (2017)
The species Libidibia ferrea belongs to the family Fabaceae, popularly known as pau-ferro or jucá, being used in traditional medicine as antibacterial, antiulcerogenic, anti-inflammatory and analgesic. Eugenia uniflora belongs to Myrtaceae family, being known as pitanga, popularly used in the treatment of diarrhea, inflammation, hyperglycemia and hypertension. An analysis of medicinal plants as a source of new drugs for the treatment of several diseases, and involvement of the inflammatory process in numerous diseases, and strong indications of pharmacological activity associated with the presence of bioactive substances present in these species, With the aim of evaluating an anti-inflammatory and antimociceptive activity of the crude extracts and phrases of Libidíbia ferreira and Eugenia uniflora, through the model of carrageenan-induced peritonitis, hot plate test and abdominal contortions induced by acetic acid in Swiss mice Species Mus musculus. From crude and crushed vegetable materials, crude extracts and Eugenia uniflora fractions (crude aqueous extract, aqueous fraction, hexane fraction and ethyl acetate fraction) and Libidibia ferrea (crude aqueous extract, extracts Crude extracted with ethanol 20, 40, 60 and 80%, fraction ethyl acetate and aqueous fraction). The chromatographic analyzes of the extracts and the fractions allowed to separate and identify the gallic acid hydrolysable tannins, with retention time of approximately 8.7 minutes, and ellagic acid, with retention time of 25.1 minutes, also detected the flavonoid myricitrin, Confirmed With the chromatographic data of the standards. In the evaluation of leukocyte migration, the crude extract fractions of Eugenia uniflora and Libidibia ferrea at doses of 50 mg / kg, 100 and 200 mg / kg reduced the number of inflammatory cells to the site of inflammation (p <0.001), comparing the treated groups With the positive control group. The decrease in the cellular influx was accompanied by a decreased marking of myeloperoxidase activity, reduction of MDA, and showed protection against glutathione depletion (p <0.001). The administration of the crude extracts and fractions produced a peripheral antinociceptive response in all the doses tested, reducing the number of product contours by means of an acoustic in mice, but demonstrating little central analgesic activity, being evaluated by the hot plate test. The results indicate that these plants are anti-inflammatory and antinociceptive activities. However, other studies are indispensable for the elucidation of its pharmacological properties, studies of inscription analysis and toxic properties.